2007
DOI: 10.1016/j.febslet.2007.08.073
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic PP1 glycogen‐targeting subunit interaction with phosphorylase a can be blocked by C‐terminal tyrosine deletion or an indole drug

Abstract: The inhibition of hepatic glycogen-associated protein phosphatase-1 (PP1-G L ) by glycogen phosphorylase a prevents the dephosphorylation and activation of glycogen synthase, suppressing glycogen synthesis when glycogenolysis is activated. Here, we show that a peptide ( 280 LGPYY 284 ) comprising the last five amino acids of G L retains high-affinity interaction with phosphorylase a and that the two tyrosines play crucial roles. Tyr284 deletion abolishes binding of phosphorylase a to G L and replacement by phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…In addition to G-6-P both glucose and glycogen are also thought to regulate the activity status of GS [51,52]. GS activity is also regulated indirectly by glycogen phosphorylase given that glycogen phosphorylase allosterically regulates PP1 activity [53]. The relative importance of each of these mechanisms affecting GS is not known although the dominance of the effects of GSK-3 inhibitors suggest, for example, that compensatory inactivation of PP1 does not occur.…”
Section: Glycogen Metabolismmentioning
confidence: 99%
“…In addition to G-6-P both glucose and glycogen are also thought to regulate the activity status of GS [51,52]. GS activity is also regulated indirectly by glycogen phosphorylase given that glycogen phosphorylase allosterically regulates PP1 activity [53]. The relative importance of each of these mechanisms affecting GS is not known although the dominance of the effects of GSK-3 inhibitors suggest, for example, that compensatory inactivation of PP1 does not occur.…”
Section: Glycogen Metabolismmentioning
confidence: 99%
“…GP inhibitors reduce blood glucose in animal models of diabetes and improve glucose tolerance in the postprandial state. An alternative strategy has been to selectively modify the interaction between GPa and the glycogen-targeting protein G L by mutating the terminal GPa binding domain or by using small molecules that prevent the interaction of GPa with G L (12). In this way, the negative control exerted by GPa on LGS activation is released without altering the activation state of GPa.…”
mentioning
confidence: 99%
“…9,10 In recent years, the interaction of GP and glycogen targeting 60 subunit (G L ) of protein phosphatase 1 (PP1) has been identified as a novel molecular target for the treatment of T2DM. [11][12][13] It was demonstrated in an in vivo mouse model that disruption of G L -GP interaction resulted in an increased glycogen synthase activity and the mice had improved glucose tolerance. 14 X-ray crystallography showed that the G L -GP interaction took place by binding the C-terminal region of G L to the allosteric site of GP.…”
mentioning
confidence: 99%